The determinants of running performance in middle distance female athletes - Mpholwane, Matome Lieghtone (My University, 2008)
ABSTRACT Male subjects are invariably used to study the physiological determinants of middle distance running performance. Studies that do include females have examined only the aerobic contribution to middle distance running performance. The aim of the present study was to investigate aerobic, anaerobic and muscle function factors that could be used to predict middle distance running performance in female runners. This study was performed at an altitude of 1800m. Eleven middle distance female runners aged 18-20 were selected for the study. Aerobic capacity was assessed by measuring the maximal oxygen consumption (VO2max), running velocity at maximal oxygen consumption (vVO2max), running economy (RE) and onset of blood lactate accumulation (OBLA). The blood lactate curve of each subject was constructed by relating the oxygen consumption, to the plasma lactate concentrations. Anaerobic capacity was determined by measuring the maximum accumulated oxygen deficit (MAOD) on a treadmill. Muscle function was assessed by having the subjects cycle as fast as possible against changing brake weights ranging from heavy to light using a Monark cycle ergometer. The brake force (kg) was related to velocity (rpm).
Keywords: running performance; maximal oxygen consumption; running economy; onset of blood lactate accumulation; maximal accumulated oxygen deficit; force velocity curve